THE INFLUENCE OF USING EDUCATIONAL GAMES ON IMPROVING VOCABULARY MASTERY IN LEARNING ENGLISH AND JAPANESE - Pasaribu, Gumarpi Rahis; Rani Arfianty; Murniati Br Barus; Nursaima Harahap; Siti Meutia Sari (LPPM STISIPOL Mujahiddin, 2024)
This study aims to explore the impact of using educational games on improving students' vocabulary mastery in learning English and Japanese. Using a quantitative and experimental approach, this study involved students who were learning both foreign languages, both at secondary school and college levels. The research sample was selected using a purposive sampling method, and the instruments used included pre-test, post-test, observation, and questionnaire. The results of the analysis showed a significant increase in students' vocabulary mastery after interacting with educational games, with a p value <0.05. In addition, observations showed that students were more active and motivated in learning using educational games compared to conventional methods. The questionnaire revealed that the majority of students felt more confident in using new vocabulary and were more motivated to learn. These findings are in line with previous studies showing that gamification elements in educational games increase student engagement and motivation. However, the effectiveness of educational games can vary depending on the type of game used and the individual learning preferences of students. This study concludes that educational games can be an effective learning tool in improving vocabulary mastery, provided that they are adjusted to students' preferences and learning styles. Further studies are recommended to explore the most influential gamification elements and combine educational games with traditional methods for more optimal results.